Vegetation structure and ecological characteristics of forest of North Andaman Islands (India) - Prasad, P.; Sringeswara, A.; Reddy, C.; Kumari, P.; Varalakshmi, R.; Raza, S.; Dutt, C. (Biological Letters, 2010)
In this study, 3-ha research plots were established, one each in evergreen, semi-evergreen, and moist deciduous forests of North Andaman Islands. These 3 vegetation types were selected to study the structural aspects of plant diversity in forest communities. Our results showed high species richness and basal area in evergreen forest, high diversity in semi-evergreen forest, and high tree density (trees ha-1) in moist deciduous forest. At family level, the Anacardiaceae and Sterculiaceae dominated all the forest types, and were distributed throughout the North Andaman Islands. In the 3 forest communities, most species exhibited clumped spatial distribution, while random distribution ranked second. Tree girth class distribution revealed a decreasing number of trees with increasing girth class, indicating natural regeneration of these forest types. The species-area curve clearly reached a plateau at 3-ha area in respect of species number, supporting the adequacy of the large plot size selected in the present investigation. The study recorded a total of 136 tree species in the 3 forest communities and was higher than in many other tropical forest sites. The vegetation analysis of 3-ha plot in 3 different forest types substantially contributed data on North Andaman site potentiality, with reference to its species richness and diversity.